Filhos adotivos: esses somos nós - Comin, Rejane (My University, 2024)
This dissertation aimed to analyze the particularities of adoption, from the perspective of adopted children over 18 years old, with the aim of integrating the experiences identified with the aspects involved in this process, as well as developing an intervention based on the observed results. Therefore, a mixed method research was carried out, involving a qualitative and quantitative combination, in a convergent manner, with a sample of adult adopted children, regardless of the age at which they were adopted. A multiple case study was carried out, using a semi-structured interview, based on the script developed by Dra. Lidia Natalia Dobrianskyj Weber. Quantitative data were collected through a survey-type questionnaire, designed with the purpose of characterizing sociodemographic aspects of the respondents and establishing the adopted children's profile that this study managed to reach, as well as exploring the experience that these children had with their adoptions. The qualitative results found were distributed into different dimensions: aspects related to the unfolding of the origin story for the foster child and the feelings that are related to adoption, as well as the convergence between them. The quantitative data were analyzed through basic descriptive statistics and with the aid of the software IBM® SPSS® Statistics v.21. From this survey, the sociodemographic characterization, information about adoption and feelings aroused in the interviewees, associated with adoptive parenthood, were highlighted. With some information, both from the interviews and the questionnaire, a word cloud was constructed. Based on the results obtained in the field research, a video was created for sharing using technological tools, with information that clarifies the topics discussed in this research and allows the actors' qualification involved in the adoption processes. [resumo fornecido pelo autor]
Esta dissertação se propôs a analisar as particularidades da adoção, a partir da perspectiva de filhos adotivos maiores de 18 anos, no intuito de integrar as experiências identificadas com os aspectos envolvidos nesse processo, bem como elaborar intervenção diante dos resultados observados. Para isso, realizou-se uma pesquisa de método misto, envolvendo a combinação qualitativa e quantitativa, de forma convergente, com amostra de filhos adotivos adultos, independentemente da idade com que foram adotados. Realizou-se um estudo de casos múltiplos, com a aplicação de uma entrevista semiestruturada, baseada no roteiro de questionário da Dra. Lidia Natalia Dobrianskyj Weber. Os dados quantitativos foram coletados por meio de um questionário do tipo survey, elaborado com a finalidade de caracterizar aspectos sociodemográficos dos respondentes e estabelecer o perfil dos filhos adotivos que esse estudo conseguiu alcançar, bem como explorar a experiência que esses filhos tiveram com suas adoções. Os resultados qualitativos encontrados foram distribuídos em dimensões distintas, que analisaram os aspectos referentes aos desdobramentos da história de origem para o filho adotivo e os sentimentos que estão relacionados a adoção, como também a convergência entre ambos. Os dados quantitativos foram analisados por meio de estatística descritiva básica e com auxílio do software IBM® SPSS® Statistics v.21. A partir deste levantamento, foram destacadas a caracterização sociodemográfica, informações sobre a adoção e sentimentos despertados nos respondentes, associados a parentalidade adotiva. Com algumas informações, tanto das entrevistas, quanto do questionário, foi construída uma nuvem de palavras. Com base nos resultados obtidos na pesquisa de campo, elaborou-se vídeo para compartilhamento por ferramentas tecnológicas, com informações que esclarecem os temas debatidos nesta pesquisa e permitem qualificar os atores envolvidos nos processos de adoção. [resumo fornecido pelo autor]
Keywords: Adoção; Parentalidade; Família; Psicologia; Adoption; Parenting; Family; Psychology